Investigating the Characteristics of the Laser Powder Bed Fusion of SiCp/AlSi10Mg Composites: From a Single Track to a Cubic Block - Ying He; Gang Xue; Haifeng Xiao; Haihong Zhu (Micromachines)
Laser powder bed fusion (LPBF) of SiCp/AlSi10Mg is promising in many industrial fields. In this paper, the characteristics of a 15 wt.% 1200 mesh SiCp/AlSi10Mg metal matrix composite fabricated by LPBF were investigated systematically, i.e., from a single track to a block. It was found that when the laser energy input was high enough, the single track was continuous and not distorted; when the laser energy input was low, the single track was unstable and wrinkled. The densification of the LPBFed composite sample was influenced significantly by the surface morphologies and geometric dimensions of the single tracks. As high as 98.9% relative density was achieved when the optimized processing parameters were used. Because of the good wettability and the interfacial reaction during the process, the interface of SiC and the matrix showed good bonding. Near the interface of SiC and the matrix, needle-shaped phase Al4SiC4 could be found both in the single track and block, and the faceted particle Si was formed in the block because of the interfacial reaction. The microhardness of the LPBFed SiCp/AlSi10Mg composites was much higher than that of the LPBFed unreinforced AlSi10Mg. A coefficient of friction of 0.178 and wear rate of 2.02 × 10−4 mm3/(N⋅m) were achieved for the LPBFed composites. The main wear mechanism was delamination wear, accompanied by abrasive wear. The maximum yield strength and ultimate compressive strength were 566.6 MPa and 764.1 MPa, respectively. The fracture mode of the LPBFed composites is mainly brittle fracture. This study provides a theoretical and technical basis for LPBFed SiCp/AlSi10Mg 3D parts.